Selective Stratagems for Ensuring Financial Stability: Taking into Account the Positions of The State and Business Entities - Тetyana CALINESCU; Ganna LIKHONOSOVA; Оlena ZELЕNKО (Communications of International Proceedings, 2022)
The variability of the environment, the need to quickly solve a number of problems caused by the global financial and economic crisis - this is an incomplete list of those prerequisites that encourage most business entities to develop financial and economic stability stratagems that will allow them to survive in conditions of uncertainty. The purpose of the study is the selective systematization of stratagems that ensure financial stability, taking into account the interests of the state and business entities, which is relevant for the support and adoption of appropriate strategies, based on the policy currently pursued by Ukraine in the international financial and geopolitical European environment. Methods/approaches: the research methodology is based on methods of qualitative comparative analysis, logical and heuristic methods, methods of extrapolation and economic-mathematical modeling. Results: the analysis of previous studies made it possible to determine that the most effective tool for taking into account the positions of the state and business entities are the factors of harmonization of relations between the government, business, public organizations and other institutions and participants in the process of stabilizing the functioning of the country's financial system. Accordingly, a model of the interaction of the interests of interested parties regarding the provision of financial stability is proposed, as well as the nature of the interaction of subjects by interests regarding the regulation and provision of financial stability and the elements of the economic space for the coordination of the interests of business subjects are defined. The study also presents an ensemble of general processes of ensuring the financial stability of the state with the help of economic and mathematical tools. Conclusions: achieving financial stability is possible only under the condition of using elements of stratagems thinking and foresight, timely response to changes in the external and internal environment of the entities.
Keywords: stratagems; financial stability; directions of development; model; elements